Young Mothers Lack Plans to Receive Preventive Health Care - Kari R. Harris; Carolyn R. Ahlers-Schmidt; Kerri L. Weeks (SAGE Publishing, 2014)
Background: Despite their health vulnerability, multiple barriers to health care exist for adolescent mothers. This pilot study aimed to gain information regarding preventive health care intentions of young mothers following pregnancy. Methods: We administered institutional review board-approved surveys to mothers aged 15 to 21 years at a local hospital where 75% of infants are born. Participants were questioned regarding current and intended use of health care. Results: Results showed that only half of the young mothers identified a primary care provider (PCP) but more had seen some type of doctor in the 3 years preceding their pregnancy. White mothers were significantly more likely than Hispanic to have seen a physician prior to pregnancy; family physicians (FPs) were referenced most. Additionally, white and black mothers were significantly more likely than Hispanic mothers or mothers of other ethnicity to have received minor emergency care during pregnancy. While FPs were referenced most frequently, few mothers planned to see one for preventive care. Nearly half of participants planned to see their obstetrician/gynecologist (OBGYN) for routine yearly checkups. Conclusions: This research indicates a gap in health care for young mothers. Only half enter parenthood with a PCP, and once mothers, few plan to see a physician for preventive care. In this study, OBGYNs were identified most often for preventive health care. Therefore OBGYNs should provide comprehensive care to this population, or connect them with other PCPs. Furthermore, young mothers do plan on seeing FPs for acute health care, supporting previous recommendations that physicians use all visits to provide comprehensive care to adolescents.